Clec7a expression in inflammatory macrophages orchestrates progression of acute kidney injury - Wang, Yaqiong; Li, Xianzhe; Xu, Xialian; Yu, Jinbo; Chen, Xiaohong; Cao, Xuesen; Zou, Jianzhou; Shen, Bo; Ding, Xiaoqiang (Frontiers in Immunology, 2022)
Acute kidney injury (AKI) is associated with high risk of mortality, post-disease renal fibrosis, kidney dysfunction and renal failure. Renal macrophages play a key role in the pathogenesis (M1 subpopulation), healing and remodeling (M2 subpopulation) in AKI and, thus, have been a promising target for clinical treatment of AKI. Here, in a mouse renal ischemia/reperfusion injury (IRI) model for AKI, we showed that renal macrophages could be further classified into Clec7a+ M1 macrophages, Clec7a- M1 macrophages, Clec7a+ M2 macrophages and Clec7a- M2 macrophages, representing distinct macrophage populations with different functionality. Interestingly, Clec7a+ M1 macrophages exhibited potent pro-inflammatory and phagocytic effects compared to Clec7a- M1 macrophages, while Clec7a- M2 macrophages exhibited better proliferating and migrating potential, which is critical for their role in tissue repairing after injury. These data from mice were further strengthened by bioinformatics analyses using published database. In vivo, combined expression of Clec7a in M1 macrophages and depletion of Clec7a in M2 macrophages significantly improved the renal function after IRI-AKI. Together, our data suggest that Clec7a is crucial for the fine regulation of macrophage phenotype during AKI and could be a novel target for boosting clinical therapy.